Use of low-dose varenicline in hospitalized smokers: A case series low-dose varenicline in hospitalized smokers - Rachael L. Joyner; Remi E. Phillips; Farid A. Manshaii; James M. Davis (SAGE Open Medical Case Reports)
Nicotine replacement therapy is the primary medication used to treat tobacco dependence in hospitalized patients. Recent evidence shows that varenicline is more effective than nicotine replacement, but varenicline side effects limit its use in the hospital. Low-dose varenicline has shown similar efficacy as standard dose, but has fewer side effects and thus may be useful in hospitalized patients. We assessed the effectiveness and tolerability of low-dose varenicline (1 mg each morning or 0.5 mg twice daily; patient choice) in hospitalized adult daily smokers between July 2022 and March 2023. The primary outcome was self-reported 7-day smoking abstinence at the first outpatient visit after hospitalization. Secondary outcomes included smoking reduction and medication tolerability. Of the 15 patients assessed, 8 (53.3%) reported 7-day smoking abstinence at their first post-discharge outpatient visit (mean of 14.9 days after discharge). Mean cigarettes per day decreased from 22.0 (SD 17.4) prior to hospitalization to 3.7 (SD 6.0) after hospitalization. Low-dose varenicline was well tolerated, with 80% (12) patients reporting no adverse events and 20% (3) patients reporting mild side effects not requiring a change in medication or dose. Study outcomes support the possibility that low-dose varenicline might be an effective and well-tolerated treatment for hospitalized smokers. Results from this case series are limited by the small sample size and lack of a control arm. Findings suggest that a randomized controlled trial may be warranted to assess the efficacy and tolerability of low-dose varenicline in hospitalized patients.